Boas práticas na Administração Pública: uma análise do modelo de gestão da EBSERH à luz do modelo de governança pública - Oliveira, Ana Lorena Lobo (2020)
The brazilian public management follows the changes brought about by the modernization movements perceived worldwide. The context prints a public administration model based on service efficiency, with the possibility of adopting good public governance practices. As a result of the modernization of practices is the Brazilian Hospital Services Company (EBSERH), a public company created to manage federal university hospitals. In this scenario, this dissertation proposed to evaluate, in the light of the public governance movement, the current management model adopted by EBSERH. The study was configured as a qualitative research, with the proposal of a public governance structure as a technological product. For the study in question, through documentary research, the documents produced by EBSERH, academic articles and reports about the institution were used as a data source. The analysis technique adopted was content analysis. The research was justified based on the premise that public governance and its principles of transparency, integrity, responsibility, accountability and equity are an alternative to improve the performance of institutions through a society that requires better performance from public managers. As results it was concluded that, through the documents produced by the company, the EBSERH emphasizes the principle of integrity to the detriment of others, compromising the entire public governance process demonstrated by the generation of value for society, which is hampered by the questioning of articles and reports about the provision of services, such as the use of the resources and lack of beds.